Mouse tissue distribution and persistence of the food-born fusariotoxins Enniatin B and Beauvericin - Rodríguez-Carrasco, Yelko (Toxicol Lett, 2016)
The fusariotoxins Enniatin B (Enn B) and Beauvericin (Bea) have recently aroused interest as food contaminants and as potential anticancer drugs. However, limited data are available about their toxic profile. Aim of this study was to investigate their pharmacological behavior in vivo and their persistence in mice. Therefore, liquid chromatography tandem mass spectrometry (LC-MS/MS) was used to analyze the distribution of Enn B and Bea in selected tissue samples and biological fluids originating from mice treated intraperitoneally with these cyclohexadepsipeptides. Overall, no toxicological signs during life time or pathological changes were observed. Moreover, both fusariotoxins were found in all tissues and serum but not in urine. Highest amounts were measured in liver and fat demonstrating the molecules´ tendency to bioaccumulate in lipophilic tissues. While for Bea no metabolites could be detected, for Enn B three phase I metabolites (dioxygenated-Enn B, mono- and di-demethylated-Enn B) were found in liver and colon, with dioxygenated-Enn B being most prominent. Consequently, contribution of hepatic as well as intestinal metabolism seems to be involved in the overall metabolism of Enn B. Thus, despite their structural similarity, the metabolism of Enn B and Bea shows distinct discrepancies which might affect long-term effects and tolerability in humans.